Joseph Wanjie, Kikuyu Catholic catechist - Araújo, Melvina [UNIFESP] (2012)
This article discusses the problem of cultural mediation, focusing on the relations between a Kikuyu catechist and Consolata missionaries. It analyzes a biography of this catechist, which was written by a missionary. The information contained in the biography is compared with data from other sources that allow us to reconstruct the trajectory of an important agent in the relations between Catholic missionaries and natives in Kenya.